2020
DOI: 10.1080/07315724.2020.1783721
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Proteasome System Activity is Suppressed by Curcumin following Exercise-Induced Muscle Damage in Human Skeletal Muscle

Abstract: PURPOSE: Curcumin is a natural polyphenolic compound with antioxidant and anti-inflammatory properties. In vitro and in vivo animal studies have demonstrated that exposure to curcumin leads to dysregulation of the ubiquitin-proteasome system (UPS). However, to date, no study has investigated curcumin's ability to influence UPS activity in a human model. Therefore, the purpose of this study was to investigate the effects of curcumin supplementation on markers of UPS activity in the presence of elevations in UPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…All extracts were supplemented with phenylmethanesulfonyl fluoride and a protease inhibitor cocktail (Sigma Chemical Company, St. Louis, MO, USA) with broad specificity for the inhibition of serine, cysteine, and metallo-proteases. Protein contents for total protein, sarcoplasm-, and nuclear-extracted samples were analyzed in duplicate and determined spectrophotometrically at a wavelength of 750 nm (Bio-Rad Hercules, CA, USA) and using bovine serum albumin as the standard [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…All extracts were supplemented with phenylmethanesulfonyl fluoride and a protease inhibitor cocktail (Sigma Chemical Company, St. Louis, MO, USA) with broad specificity for the inhibition of serine, cysteine, and metallo-proteases. Protein contents for total protein, sarcoplasm-, and nuclear-extracted samples were analyzed in duplicate and determined spectrophotometrically at a wavelength of 750 nm (Bio-Rad Hercules, CA, USA) and using bovine serum albumin as the standard [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…10,31,32,36,[52][53][54][55][56][57][58][59] Only 7 studies definitively reported lidocaine was administered without epinephrine. 23,51,[60][61][62][63][64] The majority of the authors did not report lidocaine administration with or without epinephrine (~77%). Five studies reported the use of a superficial lidocaine/prilocaine cream or lidocaine tape as a local anesthetic prior to the microbiopsy procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies (~14%) reported the use of epinephrine with lidocaine administration 10,31,32,36,52–59 . Only 7 studies definitively reported lidocaine was administered without epinephrine 23,51,60–64 . The majority of the authors did not report lidocaine administration with or without epinephrine (~77%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the public's interest on natural phytotherapy and diet therapy related to health and disease increases, this attractive and safe alternative has been extensively studied. Previous studies have also shown that curcumin alleviates postexercise skeletal muscle injury by inhibiting the activity of the ubiquitin-proteasome system [ 26 ]. Therefore, we hypothesize that curcumin may be able to improve breast cancer cachexia-related skeletal muscle atrophy.…”
Section: Introductionmentioning
confidence: 99%